The lethal cargo of Myxococcus xanthus outer membrane vesicles - Berleman, James E.; Allen, Simon; Danielewicz, Megan A.; Remis, Jonathan P.; Gorur, Amita; Cunha, Jack; Hadi, Masood Z.; Zusman, David R.; Northen, Trent R.; Witkowska, H. Ewa; Auer, Manfred (Frontiers in Microbiology, 2014)
Myxococcus xanthus is a bacterial micro-predator known for hunting other microbes in a wolf pack-like manner. Outer membrane vesicles (OMVs) are produced in large quantities by M. xanthus and have a highly organized structure in the extracellular milieu, sometimes occurring in chains that link neighboring cells within a biofilm. OMVs may be a vehicle for mediating wolf pack activity by delivering hydrolytic enzymes and antibiotics aimed at killing prey microbes. Here, both the protein and small molecule cargo of the OMV and membrane fractions of M. xanthus were characterized and compared. Our analysis indicates a number of proteins that are OMV-specific or OMV-enriched, including several with putative hydrolytic function. Secondary metabolite profiling of OMVs identifies 16 molecules, many associated with antibiotic activities. Several hydrolytic enzyme homologs were identified, including the protein encoded by MXAN_3564 (mepA), an M36 protease homolog. Genetic disruption of mepA leads to a significant reduction in extracellular protease activity suggesting MepA is part of the long-predicted (yet to date undetermined) extracellular protease suite of M. xanthus.